Effectiveness of multimodal psychotherapeutic intervention for internet gaming disorder. (August 2022) - Sharma, Manoj Kumar; Anand, Nitin; Tadpatrikar, Ashwini; Marimuthu, Palaniappan; Narayanan, Gitanjali
Highlights: Internet gaming disorder (IGD) appears to be a major emerging public mental health condition among young adults in India. Among the N=40 participants, a significant majority of N=39 (95.89%) were male participants who met the criterion for IGD and 39% (N=16) of these participants had only one (N=1) good offline friend. Around 62% (N=25) of participants reported spending more than 6 hours in a day on use of internet gaming and 47.5% (N=19) played video games for more than 5 days per week. Multimodal intervention was found to be effective in reduction of internet gaming, technology use and in enhancement among all domains of quality of life with marked changes visible in physical and psychological domains. Early identification and management of internet gaming disorder among young adults is crucial. This intervention program can be helpful for mental health professionals working in the community with emerging behavioral addictions inclusive of IGD. Abstract: Background: Large number of studies on Internet gaming disorder (IGD) have primarily focused on ascertaining its psychological correlates. Few studies have focused on developing and assessing effectiveness of multimodal psychotherapeutic intervention programs. This intervention focused on minimizing salience, pre-occupation, conflict related to gaming and enhancing the overall quality of life, inclusive of psychological health, physical health, and environmental problems in individuals with IGD. At present, there appear to be no such studies in the Indian context. Methods: In this study, we developed and assessed the effectiveness of an intervention manual for IGD. The intervention program consisted of ten 60-minutes sessions with one therapist administering sessions once in each week. The interventions included motivational enhancement strategies, cognitive restructuring, behavioral strategies and relapse prevention. The outcomes from intervention were measured in terms of improvement in IGD, IAT, and overall quality of life. Our assessments, both at baseline and post-intervention consisted of Internet Addiction Test (IAT), Internet Gaming Disorder Test (IGD-20) and the Whoqol-Bref. A total sample of 40 was selected out of which 33 individuals completed the 10 sessions of multimodal psychotherapy program and post assessments. Results: A total of 40 participants (age: M = 20.25, SD = 5.39) enrolled, out of which 33 completed the entire intervention program of 10 sessions and showed significant improvements. The IAT and IGD-20 showed significant difference in the scores for before treatment (M = 52.88, SD = 16.25) and after treatment (M = 42.87, SD = 11.31; t (32) = 5.10, p = 0.000) conditions; and right before treatment (M = 56.88, SD = 19.25) and after treatment (M = 47.87, SD = 15.31; t (32) = 6.94, p = 0.000) conditions respectively. The internet addiction and internet gaming disorder scores showed a similar degree of severity reductions on the IAT and IGD-20 respectively at the end of week 8. In addition, the participants showed significant improvements in the quality of life inclusive of physical and psychological health post the completion of intervention program. Limitations: The sample size of the study was small and assessments for evaluation of other psychological symptoms like depression, anxiety could have been conducted. Conclusion: The intervention program indicated a substantial change in the IGD scores at post- assessment. A study on a larger sample to assess the validity of the manualized multimodal psychotherapy program for IGD needs to be conducted. In addition, this manualized intervention program can be useful for administering structured intervention for IGD by mental health professionals working in the area of internet gaming disorder.